The Invasion and Metastasis of Colon Adenocarcinoma (COAD) Induced by SALL4 - Wenjuan Zhang; Yan Hu; Wenbing Zhang; Ke Yi; Xiaohui Xu; Zhihua Chen (Journal of Immunology Research)
Objective. The development and progression of many cancers may be related to SALL4, the role and molecular mechanism of which are unclear in colon adenocarcinoma (COAD). Methods. The SALL4 expression in adjacent normal mucosa tissues and carcinoma tissues of patients with COAD was detected through bioinformatic analysis based on TCGA database and immunohistochemistry. Single-cell analysis showed that the expression of SALL4 in normal tissue was noticeably low. GSEA analysis suggested that the SALL4 upregulated the GO and pathway of growth and cancer development and downregulated metabolization pathway. The relationship between lymph node metastasis, histological grading, clinical staging, and the expression of SALL4 in carcinoma tissues was analyzed. The upregulated or downregulated SALL4 expression of COAD cell lines was established. The influence of SALL4 on COAD cells invasion and proliferation was detected using plate cloning assay and Transwell. The expressions of EMT-related proteins E-cadherin, N-cadherin, vimentin, and Twist were detected by Western blot. The EMT phenotype was analyzed by immunofluorescence. Results. The study confirmed that the expression of SALL4 was upregulated in COAD and positively correlated with the degree of tumor differentiation, tumor staging, and metastasis. The overexpression of SALL4 was related to a poor prognosis, promoted the invasion and proliferation of colorectal cancer cells, and accelerated the occurrence of EMT, which was characterized by upregulation of Twist, vimentin, and N-cadherin expressions and downregulation of E-cadherin. The immunofluorescence staining confirmed the EMT phenotype. On the contrary, knocking out SALL4 gene reversed EMT, weakened cell proliferation and invasion, inhibited upregulation of Twist, vimentin, and N-cadherin expressions and downregulation of E-cadherin. Conclusion. To sum up, TNM grading, histological grading, and lymphatic metastasis were significantly correlated with SALL4 in tumor tissues. SALL4 played a vital role in tumor proliferation, invasion, and tumor EMT and may be a novel target for COAD.